Fmoc-POAC: [(9-fluorenylmethyloxycarbonyl)-2,2,5,5-tetramethylpyrrolidine-N-oxyl-3-amino-4-carboxylic acid]: A novel protected spin labeled beta-amino acid for peptide and protein chemistry - Tominaga, M.; Barbosa, SR; Poletti, E. F.; Zukerman-Schpector, J.; Marchetto, Reinaldo [UNESP]; Schreier, S.; Paiva, ACMM; Nakaie, C. R. (Pharmaceutical Soc Japan, 2001)
The stable free radical 2,2,6,6-tetramethylpiperidine-N-oxyl-4-amino-4-carboxylic acid (TOAC) is the only spin labeled amino acid that has been used to date to successfully label peptide sequences for structural studies. However, severe difficulty in coupling the subsequent amino acid has been the most serious shortcoming of this paramagnetic marker. This problem stems from the low nucleophilicity of TOAC's amine group towards the acylation reaction during peptide chain elongation. The present report introduces the alternative beta -amino acid 2,2,5,5-tetramethylpyrrolidine-N-oxyl-3-amino-4-carboxylic acid (POAC), potentially useful in peptide and protein chemistry. Investigations aimed at addressing the stereochemistry of this cyclic molecule through X-ray diffraction measurements of crystalline and bulk samples revealed that it consists only of the trans conformer. The 9-fluorenylmethyloxyearbonyl group (Fmoc) was chosen for temporary protection of the POAC amine function, allowing insertion of the probe at any position in a peptide sequence. The vasoactive octapeptide angiotensin II (AII, DRVYIHPF) was synthesized by replacing Pro(7) with POAC. The reaction of Fmoc-POAC with the peptidyl-resin occurred smoothly, and the coupling of the subsequent amino acid showed a much faster reaction when compared with TOAC. POAC(7)-AII was obtained in good yield, demonstrating that, in addition to TOAC, POAC is a convenient amino acid for the synthesis of spin labeled peptide analogues. The present findings open the possibility of a wide range of chemical and biological applications for this novel beta -amino acid derivative, including structural investigations involving its differentiated bend-inducing characteristics.
Keywords: peptide; spin label; electron paramagnetic resonance; amino acid; TOAC; POAC